Embedding research for innovation to meet societal needs in national research systems: experiences from Ghana - Osei-Amponsah, Charity; Sakyi-Dawson, O.; Adjei-Nsiah, Samuel; Adu-Acheampong, R.; Owuso Essegbey, George; Quarmine, W. (EDP Sciences, 2016)
The experiences synthesised in this article indicate how significant effects in two agricultural domains have been achieved by creating pathways for inter-dependent socio-technical and institutional changes, at a range of levels of action, governance and policy-making. The synthesis emphasizes the importance of co-learning, experimentation, and critical reflection among a wide network of ‘champions’ of transformational change on behalf of smallholder farmers and processors. It shows that innovation processes may involve actors along entire value chains, industry leaders at national level, or local level actors seeking to widen the space for change beyond their immediate circle of direct influence. While the research and development initiatives of the domains are shown to have been critical in identifying the constraints and opportunities of smallholders, and also to the effects documented, this was largely because the research effort converged around empirically grounded problems and opportunities identified. The information sought, and the solutions found useful, were determined by the members of innovation platforms that drove the processes of change.